Determinants of Socio Economic and Demographic Characteristics of Poverty in Aceh Province - Heri Wintara; Raja Masbar; Suriani Suriani (Research Collaboration Community (RCC), 2021)
This study analyzes the effect of socio-economic and demographic characteristics on poverty levels in Aceh Province in the short and long run. Socio-economic characteristics are represented by factors of income per capita, open unemployment rate, and cigarette consumption. While the demographic characteristics are represented by the dependency ratio factor. This study uses panel data from 23 districts/cities in Aceh Province for the 2010-2019 period and the analysis model used is the Autoregressive Distributed Lag (ARDL) panel model. The results found in this study are the dependency ratio factor, cigarette consumption, and the open unemployment rate have a significant effect in the long run on the percentage of poor people. Meanwhile, the significant factors in the short run are the dependency ratio and the open unemployment rate.